A Longitudinal Assessment of Parenting Stress in Parents of Children with New-Onset Epilepsy. (14th October 2020) - Bakula, Dana M; Wetter, Sara E; Peugh, James L; Modi, Avani C
Abstract: Objective: Parents of children with newly diagnosed epilepsy may experience elevated parenting stress. The present study examined trajectories of parenting stress over time and identified modifiable predictors of these trajectories. Methods: Parents of youth with epilepsy ( N  = 102; 2–12 years old) completed questionnaires 1, 4, 13, 19, and 25-months post-diagnosis, including measures of parenting stress, family functioning, child psychosocial functioning, sociodemographics, and perceived stigma. Latent growth curve models (LGCM) were used to examine domains of parenting stress over time. Results: At baseline, 25–48% of parents reported elevated parenting stress. LGCMs revealed that the parent and child domains of parenting stress were generally stable across time. However, life stress was more variable across time, and parents with higher initial life stress had a greater reduction in life stress over time. Socioeconomic status was identified as a non-modifiable predictor of life stress. Family functioning was associated with greater parenting stress in the parent domain. Child psychosocial functioning was associated with greater parenting stress in the parent and child domains. Conclusions: Parenting stress was elevated for a subset of families and appeared to be relatively stable over time, with the exception of life stress, which was more variable. With early screening, child factors and parent appraisals of epilepsy may be valuable targets for clinical intervention with families of children with epilepsy.